(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The aim of the article is to present the urban settlement network in designed Środkowopomorskie voivodeship. Selected development factors were analyzed, with particular regard to historical and natural conditions. The structure of the urban network was discussed. Analysis of hierarchical and concentration of urban centers was presented. The analysis leads to the conclusion thaturban settlement network designed Środkowopomorskie voivodeshiphas historically shaped network with sufficient numbers of nodes, related communication routes–land, water, air, as well as socio-economic ties